Comparison of safety and effectiveness of medical adhesive and metal spring coil in preoperative localization of peripheral pulmonary nodules - Wang, Yifei; Yue, Zhenhua; Shi, Xiaoqian; Xia, Guozhan; Qin, Linlin; Sun, Qi; Huang, Yiling; Chen, Rong; Zhao, Xuewei; Wang, Mingdong (Frontiers in Medicine, 2025)
BackgroundAccurate preoperative positioning is the key to the success of thoracoscopic surgery for small pulmonary nodules. There are many methods for locating pulmonary nodules in clinical practice, but there are currently few research reports on the value of medical adhesive localization.ObjectiveTo compare the clinical value of two positioning methods, medical adhesive and metal spring coil, in the preoperative application of VATS through retrospective analysis.MethodsA total of 288 patients who underwent thoracoscopic surgery in our hospital from January 2021 to June 2024 due to the discovery of solitary pulmonary nodules during chest CT examination were included in this study. Preoperative patients were randomly divided into two groups, with 205 patients undergoing preoperative medical adhesive positioning (Group A) and 83 patients undergoing metal spring coil positioning (Group B). After the positioning was completed, record the positioning time of each group of patients and the immediate pain score 15 min after the positioning was completed, the complications located in each group of patients, and whether there was positioning failure or not.ResultsThe localization success rate of the medicine adhesive positioning group [99.5% (204/205)] was higher than that of the metal spring coil positioning group [91.6% (76/83)] (P = 0.001). The positioning time of the medical adhesive positioning group was 12.00 (10.00, 14.00) min, which was shorter than the 13.00 (11.00, 16.00) min of the micro coil group (P = 0.001). The immediate pain score (2.32 ± 0.79) of the medical adhesive positioning group 15 min after positioning was significantly lower than that of the metal spring coil positioning group (3.97 ± 0.54) (P < 0.001). The incidence of complications such as pneumothorax [15.7% (13/83) vs 5.4% (11/205), P = 0.004], pulmonary hemorrhage/hemoptysis [20.5% (17/83) vs 4.9 (10/205), P < 0.001] was significantly higher in the metal coil positioning group than in the medical adhesive positioning group.ConclusionPreoperative medical adhesive positioning for pulmonary nodules is safe, reliable, and effective. Compared with metal spring coil positioning, it has shorter positioning time, milder pain after positioning, lower incidence of positioning related complications, and more flexible arrangement of surgical timing after positioning. It has high clinical application value.